1344 Serum Silicon During the First Year of Life. (October 2012) - Díaz-Gómez, NM; Doménech, E; Bisse, E; Barroso, F; Martin, LM
Abstract : Background and Aims: Serum silicon (SSi) declines with age. Silicon is known to have positive effects on bone metabolism, but SSi in preterm infants and its relationship with other oligoelements have received little attention. To study changes in SSi levels during the first year of life in preterm infants and to determine (a) whether there are differences compared with term newborns and one-year-old healthy infants, (b) their relationship with serum zinc and copper levels. Methods: We studied: 42 preterm infants (GA: 32±1.8 wk.; birthweight: 1651±281 g) assessed at 36 and 40 weeks post-conceptional age (PCA) and at 12 months corrected age (CA), 30 healthy full-term newborns aged 2–3 days and 30 healthy full-term infants aged 12 months. At each evaluation, we recorded anthropometric measurements, serum Si, Zn, Cu (atomic absorption spectrometry) and bone alkaline phosphatase (immunoradiometric assay). Results: Preterm infants showed significantly higher SSi levels than non-preterm infants in all measurements. Although SSi decreased significantly between 40 weeks PCA and 12 months CA, it remained higher than in non-preterm infants. At 40 weeks PCA, zinc levels were lower while copper and bone alkaline phosphatase were higher in preterm infants. At 12 months the differences were not significant. There were no significant correlations between serum silicon, zinc and copper concentrations in any of the groups. Conclusions: SSi concentration in preterm newborns was significantly higher than in full-term newborns. Although it decreased during the first year of life, SSi remained higher than in full-term infants aged 12 months.